Effect of etomidate and propofol induction on hemodynamic and endocrine response in patients undergoing coronary artery bypass grafting/mitral valve and aortic valve replacement surgery on cardiopulmonary bypass - Kaushal, Ram Prasad (Ann Card Anaesth, 2015)
INTRODUCTION: The concerns for induction of anaesthesia in patients undergoing cardiac surgery include hemodynamic stability, attenuation of stress response and maintenance of balance between myocardial oxygen demand and supply. Various Intravenous anaesthetic agents like Thiopentone, Etomidate, Propofol, Midazolam, and Ketamine have been used for anesthetizing patients for cardiac surgeries. However, many authors have expressed concerns regarding induction with thiopentone, midazolam and ketamine. Hence, Propofol and Etomidate are preferred for induction in these patients. However, these two drugs have different characteristics. Etomidate is preferred for patients with poor left ventricular (LV) function as it provides stable cardiovascular profile. But there are concerns about reduction in adrenal suppression and serum cortisol levels. Propofol, on the other hand may cause a reduction in systemic vascular resistance and subsequent hypotension. Thus, this study was conducted to compare induction with these two agents in cardiac surgeries. METHODS: Baseline categorical and continuous variables were compared using Fisher's exact test and student's t test respectively. Hemodynamic variables were compared using student's t test for independent samples. The primary outcome (serum cortisol and blood sugar) of the study was compared using Wilcoxon Rank Sum test. The P value less than 0.05 was considered significant. RESULTS: Etomidate provides more stable hemodynamic parameters as compared to Propofol. Propofol causes vasodilation and may result in drop of systematic BP. Etomidate can therefore be safely used for induction in patients with good LV function for CABG/MVR/AVR on CPB without serious cortisol suppression lasting more than twenty-four hours.